O ensino superior de relações públicas : formação digital, práticas e desafios na UFSM - Rhoden, Valmor (2013)
The goal of this thesis is to analyse the Digital Public Relations in Higher Education and verify, through case study, its insertion at the Federal University of Santa Maria. Throughout the development of the study, we sought to answer the following question: How the higher education of Public Relations inserts new digital technologies in the training of their students? To this end, we conducted a literature on the topic, including books, dissertations and thesis, annals of events and scientific journals of Communication and Education. The theoretical category Public Relations Digital was developed from Stasiak (2009), with the concept of WebRP, associated with the Digital Journalism, in view Machado (2003, 2007, 2010). In the teaching of Public Relations, the lead author was Moura (2001, 2002, 2007, 2008, 2009). The methodology chosen for the thesis is supported by case study (Yin, 2005) and the discursive textual analysis of Galiazzi and Moraes (2011) to obtain the results in terms of curricular practices offered by the two courses in the Federal University of Santa Maria. Was also carried out an interview with the guidelines for course coordinators and the teacher who participated in the creation of the course area in the Higher Education Center North-RS, Federal University of Santa Maria, and coordinated the last update of the course curriculum in Santa Maria. On a broader level, we analyzed the Normative Resolution nº. 43 of the Federal Council of Public Relations governing the areas of professional activity in the country - the National Curriculum Guidelines of 2002 and 2013, approved by the Ministry of Education. In its development, the study relied on theoretical and empirical research, analyzing results and relating them to the authors adopted as the basis for further thematic. The results showed a gap regarding the insertion of digital courses surveyed. This research aims to contribute to the academic community understand the relevance in discussions of the profession, which requires knowledge of the digital resources of modern times.